Hubungan Jenis Kelamin, Obesitas, dan Riwayat Trauma Lutut dengan Kejadian Osteoarthritis Genu di Poli Ortopedi RSUD Kota Mataram - Cokorda Dhimas Satrya Widana; Henry Pebruanto; Deny Sutrisna Wiatma; I Ketut Gede Artha Bujangga (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Osteoarthritis (OA) is a degenerative disease that causes all joint structures to stiffen, which leads to a decrease in a person's quality of life. The cause of osteoarthritis is not yet known for certain, but a number of studies have mentioned risk factors for osteoarthritis such as age, genetics, gender, obesity, knee trauma, and growth disorders. Research objective to determine the relationship between gender, obesity, and history of knee trauma with the incidence of genu osteoarthritis at the Orthopedic Polyclinic of Mataram City Hospital in 2024. Research method Quantitative descriptive analytical research with cross-sectional research design. The sampling technique used purposive sampling. The study was conducted at the Orthopedic Polyclinic of Mataram City Hospital in October 2024. The research sample was 102 respondents. The data obtained were analyzed using the Chi-square test with a significance value of p 0.05. Results of the total 102 respondents, the results of univariate analysis showed that 64.7% had osteoarthritis genu, most respondents were women as much as 66.7%, 72.5% were obese, and as many as 60.8% had a history of knee trauma. The results of bivariate analysis showed that there was a relationship between gender and the incidence of osteoarthritis genu with (p-value 0.004), there was a relationship between obesity and the incidence of osteoarthritis genu with (p-value 0.009), and there was a relationship between a history of knee trauma and the incidence of osteoarthritis genu with (p-value 0.000). There are significant relationship between gender, obesity, and history of knee trauma with the incidence of osteoarthritis genu at the Orthopedic Polyclinic of Mataram City Hospital in 2024. Keywords: Gender, Obesity, History of Knee Trauma, Osteoarthritis Genu  ABSTRAK Osteoarthritis (OA) merupakan suatu penyakit degeneratif yang menyebabkan seluruh dari struktur sendi mengalami kekakuan yang menyebabkan menurunnya kualitas hidup pada seseorang. Penyebab dari osteoarthritis belum diketahui secara pasti, namun dari sejumlah penelitian menyebutkan faktor risiko osteoarthritis seperti usia, genetik, jenis kelamin, obesitas, trauma lutut, dan kelainan pertumbuhan. Tujuan penelitian untuk mengetahui hubungan antara jenis kelamin, obesitas, dan riwayat trauma lutut dengan kejadian osteoarthritis genu di Poli Ortopedi RSUD Kota Mataram tahun 2024. Metode penelitian  yang digunakan penelitian kuantitatif deskriptif analitik dengan desain penelitian cross sectional. Teknik pengambilan sampel menggunakan purposive sampling. Penelitian dilakukan di Poli Ortopedi RSUD Kota Mataram pada bulan Oktober 2024. Sampel penelitian sebanyak 102 responden. Data yang diperoleh dianalisis dengan uji Chi-square dengan nilai signifikasi p 0,05. Hasil penelitian dari total 102 responden, hasil analisis univariat menunjukan 64,7% mengalami osteoarthritis genu, sebagian besar responden adalah perempuan sebanyak 66,7%, 72,5% mengalami obesitas, dan sebanyak 60,8% memiliki riwayat truma lutut. Hasil analisis bivariat menunjukan terdapat hubungan antara jenis kelamin dengan kejadian osteoarthritis genu dengan p-value 0,004, terdapat hubungan antara obesitas dengan kejadian osteoarthritis genu dengan p-value 0,009, dan terdapat hubungan antara riwayat trauma lutut dengan kejadian osteoarthritis genu dengan p-value 0,000. Terdapat hubungan yang signifikan antara jenis kelamin, obesitas, dan riwayat trauma lutut dengan kejadian osteoarthritis genu di Poli Ortopedi RSUD Kota Mataram Tahun 2024. Kata Kunci: Jenis Kelamin, Obesitas, Riwayat Trauma Lutut, Osteoarthritis Genu